Pembentukan Portofolio Optimal Saham-Saham Di Bursa Efek Indonesia (Bei) - Hendrato Setiabudi Nugroho; Seto Satriyo Bayu Aji (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2019)
This research was conducted with the aim of compiling an optimum portfolio of stocks listed on the Indonesia Stock Exchange (IDX) using a single index model. The subjects of this study are stocks that consistently entered into LQ45 during the 2014-2018 period. This period was chosen because at that time the stock transactions on the Indonesia Stock Exchange was bad, as evidenced by the weak and tendency of the index (IHSG) trend. The single-index model is used because it is a simple model and is widely used in optimum portfolio formation. This model can be used to calculate expected return and portfolio risk making it possible to form an optimum portfolio. Even though similar studies have often been carried out, the very dynamic movement of stock prices on the stock exchange causes changes in the optimal portfolio each year. So that research needs to be done that continuously uses different periods of the year. The results of this study indicate that of the 24 listed issuers that were sampled, only 18 shares formed the optimal portfolio. These shares were BBCA 17.21%, PWON 16.35%, WIKA 12.95%, KLBF 7.45%, GGRM 6.51%, BBNI 5.68%, UNVR 5.35%, UNTR 4, 92%, ICBP 4.65%, ADRO 3.81%, JSMR 3.21%, ASII 3.00%, SMGR 2.78%, TLKM 2.08%, PTBA 2.07%, INDF 1.90% , BMRI 0.06%, and INTP 0.02%.